Intervention for bilingual children with speech sound disorders: A description of three English/isiXhosa speaking children - Rossouw, Katherine (Division of Communication Sciences and Disorders, 2017)
IsiXhosa is a language that is widely spoken in South Africa. Bilingualism is common in South Africa, with many children learning isiXhosa as a home language and English from a young age. This study investigated three case studies of bilingual children with speech sound disorders. It aimed to describe changes in their speech following intervention according to a tailor made intervention plan. The project aimed to add to the limited research available on intervention for bilingual children with speech sound disorders. The speech of Gcobisa* (4;2), Lulama* (4;0) and Ntando* (3;0) were assessed and their speech sound disorders categorized according to Dodd's diagnostic subcategories. From this, intervention was planned and the language of intervention was selected. Following intervention, the speech of the children was reassessed. Gcobisa's speech was categorized as a consistent phonological delay, and she was provided with intervention using a minimal pairs approach with isiXhosa targets, and showed evidence of generalizing the target phoneme to English words. Lulama's speech was categorized as a consistent phonological disorder, and she received intervention based on an adapted cycles approach in English, with little evidence of change in her phonological systems in English and isiXhosa, but increased intelligibility. Ntando's speech, although more difficult to categorize, was categorized as presenting with a consistent phonological disorder, and he received intervention based on core vocabulary in English. He showed an increase in his consistency and intelligibility in both English and isiXhosa. The data has theoretical implications regarding bilingual development of isiXhosa-English, as it highlights the ways bilingual development may differ from the monolingual development of this language pair, as well as adding to the small set of intervention studies investigating the changes in the speech of bilingual children following intervention. In addition, clinical implications can be drawn, as it provides a possible framework to guide intervention for isiXhosa-English bilingual children with speech sound disorders. *Pseudonyms were used to ensure anonymity.